If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3y + -13) + -4y = -21 Reorder the terms: 5(-13 + 3y) + -4y = -21 (-13 * 5 + 3y * 5) + -4y = -21 (-65 + 15y) + -4y = -21 Combine like terms: 15y + -4y = 11y -65 + 11y = -21 Solving -65 + 11y = -21 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '65' to each side of the equation. -65 + 65 + 11y = -21 + 65 Combine like terms: -65 + 65 = 0 0 + 11y = -21 + 65 11y = -21 + 65 Combine like terms: -21 + 65 = 44 11y = 44 Divide each side by '11'. y = 4 Simplifying y = 4
| -6m-10m=-16 | | -24=5b+b | | -25=-10x+5x | | -8n-n=-18 | | 14x-25=12x+25 | | 2n+2+4n=2 | | 6x-1=5x+6 | | -11k+9k=-20 | | -11-2k=1+k | | 4b+10b=28 | | 2(k-3)=6 | | n-13+5n=-25 | | 4u-8=-28 | | x-7-12x=37 | | (14)-(-4)= | | cos(3x-180)=-1 | | 8(b+29)=24 | | g=3f+13 | | -(x-2)+3x=-3(x+4)+15 | | 6=-3+36 | | 41=-5x+6 | | 6+6n=-2-2n | | x=6y+11 | | t^3-3t^2+3t-2=0 | | 4(v+2)-11=9 | | 5x+8y=775 | | 3.5+y=1.05 | | (7p-8)(8p+9)=0 | | 2(v-5)-15=-3 | | 10+4y=8 | | 6-3x+2(4x-5)=12+2x-(4x+3) | | x+4-11= |